Home Buying and Your Credit Report - Martie Gillen; Virginia Peart (EDIS)
Before you purchase a house, you need to look over your credit report. Your credit history will affect whether or not a bank will give you a loan, as well as the interest rate you will be charged. This revised 3-page fact sheet was written by Martie Gillen and Virginia Peart, and published by the UF Department of Family, Youth and Community Sciences, July 2012.